Agri-business firms and Irish agriculture in the decades to independence - Frank Barry (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2022)
Most agricultural output in early 20th century Ireland was consumed on the farm or exported in an unprocessed state. A significant share nevertheless served as an input to Irish industry. While farmers and agri-business firms operated on opposite sides of the market, their relationship was symbiotic: the health of one impacted on the health of the other. Success on the part of agri-business firms improved agricultural market conditions in Ireland, and successful firms frequently contributed to improvements in the quality of agricultural produce.
Keywords: 330; Economic History; Agri-business firms; Irish agriculture; Early 20th century